Comparative Antioxidant and Antiradical Potentials of Four Curcuma species - B., Alansheeja D.; Nair, Mangalam S. (Sciences of Phytochemistry, 2025)
Various species belonging to the genus Curcuma are widely utilised in Asian cuisine and medicine. Among the various Curcuma species, Curcuma longa has well-established therapeutic and antioxidant effects. This study evaluated and compared the antioxidant and antiradical properties of four Curcuma species commonly used in India. The methanolic extracts were tested for DPPH radical scavenging activity, total phenolic content, total flavonoid content, total antioxidant activity (phosphomolybdenum method and beta-carotene linoleate model), hydrogen peroxide scavenging, reducing power, and metal chelating ability using various in vitro assays. According to the study, Curcuma zedoaria has the strongest antioxidant capacity, whereas Curcuma amada has a high total flavonoid concentration and metal chelating ability. When tested using the phosphomolybdenum technique, Curcuma malabarica had the highest value for antioxidant activity.